DEVELOPMENT AND STANDAIZATION OF CHIPS AND NOODLES FROM CHICOREUS RAMOSUS MEAT (International Journal of Food and Nutritional Sciences, 2022)
Chicoreus ramosus meat is edible seafood that is found in Thoothukudi district. So changed that muscle to value-added products. It has a significant role in brain development. Foods made from Chicoreus ramosus meat boost health. The objectives: To analyse the toxicity, biochemical, amino acid, and microbial content and shelf life of the Chicoreus ramosus whelk meat, to prepare the Chicoreus ramosus whelk meat powder and standardize Chicoreus ramosus whelk meatproducts, chips, and noodles, clean the whelk muscle, boil it for 1 hour, and keep it in a hot air oven for 46 hours.